GHG Inventory Research Assistance Systems - Mohd AIwi, Mohd Raimi (Universiti Teknologi Petronas, 2006)
Oneof the important actions in reducing the Greenhouse Gas (GHG) emission is by monitoring it. GHG Inventory is one of the waysto record all related data regarding the GHG emission. It is important for a country to record GHG Inventories. Research Officers (RO) from Pusat TenagaMalaysia (PTM) is responsible for the process in Malaysia. A system is to be study and developed and it has its own objectives; the ability for the whole system to assist the Research officers in doing the GHG Inventory research and managing the data and information. The Research Officers will be able to record data for the GHGInventory for morethan one baseyear, they can monitor and update the data for any changes and then the system will help them in producing any relevant reports required for the research. The system will also be able to help a new user with no experience in GHG Inventory to do the work as guidance and the information are given to the users. The objectives are definedfrom the problem occurred in the current system usedby the RO in the organization. The data and information for GHG Inventory cannot be recorded dynamically, and the process is complicated which requires more time, cost and other resources. This study has been utilizing computer technology to ease in managing the data and information in GHG Inventory. The system was developed by using the phased development methodology which will breaks the overall system into a series of versions that are developed sequentially. Many findings have been made and new ideas are implemented to improve the system.